Architectural colour in the professional palette - McLachlan, Fiona, 1958- (Routledge, 2012)
How do architects use colour? Do they adopt a different strategy or starting point for every project? Do they gradually cultivate individual colour palettes, which develop alongside their body of built work? Do they utilise, or are they aware of, the body of theoretical work that underpins the use of colour in the past, and forms the basis of most of the colour systems commercially available today? Informed by the author's thirty years in architectural practice and academia, this book investigates, documents and analyses the work of a number of contemporary architects in order to res.